2012
DOI: 10.1038/srep00514
|View full text |Cite
|
Sign up to set email alerts
|

Information Processing Capacity of Dynamical Systems

Abstract: Many dynamical systems, both natural and artificial, are stimulated by time dependent external signals, somehow processing the information contained therein. We demonstrate how to quantify the different modes in which information can be processed by such systems and combine them to define the computational capacity of a dynamical system. This is bounded by the number of linearly independent state variables of the dynamical system, equaling it if the system obeys the fading memory condition. It can be interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
434
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 335 publications
(499 citation statements)
references
References 26 publications
10
434
0
Order By: Relevance
“…In this spirit, the linear memory capacity [7] has been studied as well as the apparent tradeoff between linear memory and nonlinearity [8]. More recently it has been shown that any dynamical system (under some mild conditions) obeying the fading memory property (which is equivalent to the ESP) essentially has the same amount of computational power with respect to the number of observable variables of the system [9]. Dynamical systems with the ESP do however vary by the precise type of computations they offer, which need to be well-adjusted to the requirements of the application.…”
Section: Echo State Property Revisitedmentioning
confidence: 99%
“…In this spirit, the linear memory capacity [7] has been studied as well as the apparent tradeoff between linear memory and nonlinearity [8]. More recently it has been shown that any dynamical system (under some mild conditions) obeying the fading memory property (which is equivalent to the ESP) essentially has the same amount of computational power with respect to the number of observable variables of the system [9]. Dynamical systems with the ESP do however vary by the precise type of computations they offer, which need to be well-adjusted to the requirements of the application.…”
Section: Echo State Property Revisitedmentioning
confidence: 99%
“…In principle, any dynamical system which has a high-dimensional phase space is a good candidate for RC [25]. The RC concept offers a highly attractive approach to neuromorphic computation in hardware.…”
Section: The Hardware Reservoirmentioning
confidence: 99%
“…A periodic system is characterized by high values for DET (9) and L max (10). In addition, as stressed before, it has low complexity as expressed by low values of ENTR and SWRP.…”
Section: Visualization and Classification Of Reservoir Dynamicsmentioning
confidence: 99%
“…Reservoir computing is a class of state-space models characterized by a fixed state transition structure, the reservoir, and a trainable memoryless readout layer [7]- [9]. A reservoir must be sufficiently complex to capture all salient features of the inputs, behaving as a time-dependent, nonlinear kernel function, which maps the inputs into a higher dimensional space.…”
mentioning
confidence: 99%